Sistem Informasi Administrasi Keuangan Siswa Pada Sekolah Dasar ABC Jambi - Andaiyani, Nofita; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2023)
The process of managing student financial administration at ABC Elementary School is currently still manual, that is, it still uses books and is not well computerized. This resulted in problems, namely the administrative process took a long time and all parties could not get financial information quickly and accurately. This study aims to analyze and design a student financial administration information system which is expected to make it easier for all parties in the administrative management process. The method used in this research is prototype. Design tools using UML (Unified Modeling Language) and Adobe XD. This system provides services in the form of a menu login, register, upload transactions, manage transactions and print transactions. It is hoped that the design of this information system can be developed so that it becomes an application that can be used and applied to ABC Elementary School and for further research it can design an overall system that is integrated with other Information Systems that summarizes all business processes in school.